2013
DOI: 10.3109/0886022x.2013.809006
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 attenuates tubulointerstitial inflammation and fibrosis in subtotally nephrectomized rats

Abstract: Tubulointerstitial fibrosis is a common pathway that leads to kidney failure, and persistent tubulointerstitial inflammation is a key event in the development of tubulointerstitial fibrosis. The new immunosuppressive drug FTY720 modifies lymphocyte migration into injured tissues by sequestering lymphocytes within secondary lymphoid organs. However, its therapeutic effect on tubulointerstitial inflammation and fibrosis had not been well understood. This study was designed to explore the effect of FTY720 on tubu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…a model of proteinuria-induced tubulointerstitial fibrosis). S1P receptor modulator FTY720 (FINGOLIMOD ® ) has been shown to have an inhibitory effect on fibrosis and on T cell mediated inflammation [2629]. Therefore this intervention was used to distinguish the effects of anti-fibrotic treatment on different components of ECM remodeling pathways in the kidneys, as well as on collagen fragments in plasma and urine.…”
Section: Introductionmentioning
confidence: 99%
“…a model of proteinuria-induced tubulointerstitial fibrosis). S1P receptor modulator FTY720 (FINGOLIMOD ® ) has been shown to have an inhibitory effect on fibrosis and on T cell mediated inflammation [2629]. Therefore this intervention was used to distinguish the effects of anti-fibrotic treatment on different components of ECM remodeling pathways in the kidneys, as well as on collagen fragments in plasma and urine.…”
Section: Introductionmentioning
confidence: 99%
“…FTY720, a well-documented immunosuppressive agent, is associated with a variety of biological activities, including anti-allograft rejection (Gao et al, 2014;Koch et al, 2016), anticancer (Estrada-Bernal et al, 2012;Lu et al, 2014), anti-inflammation (Aktas et al, 2010;Xu et al, 2014), and antifibrosis (Kramer et al, 2009;Ni et al, 2013). These activities were achieved through the alteration of multiple cell phenotypes, such as viability, proliferation, apoptosis, migration/invasion, and/or epithelial mesenchymal transition, depending on specific disease conditions (Bohler et al, 2009;Lu et al, 2014;Wolf et al, 2009;Zhang et al, 2010;Zhang et al, 2014;Zhang L et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 also induces apoptosis in multiple cancer cell lines (Chen et al, 2014;Estrada-Bernal et al, 2012;Lu et al, 2014;Marvaso et al, 2014;Zhang et al, 2010), showing promise as an anticancer therapy. Recent studies showed that FTY720 controls interstitial fibrosis and extracellular matrix accumulation by inhibiting the production of inflammatory cytokines, suggesting its antifibrotic potential (Ni et al, 2013). In this study, we hypothesized that FTY720 attenuates HS formation by directly targeting HSFs.…”
Section: Introductionmentioning
confidence: 91%
“…Additionally, Jo et al described its cytoprotective effects in proximal tubular cells during renal ischemia-reperfusion injury [11] . More recently, we demonstrated that FTY720 exerts an anti-fibrotic effect in subtotally nephrectomized rats [10] . The mechanism by which FTY720 mediates protection in proteinuric nephropathy is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…FTY720 treatment alleviated this inflammatory response [3] . Previous studies have demonstrated a remarkable protective effect of FTY720 in models of 5/6 nephrectomized renal failure [10] , acute renal ischemia-reperfusion injury [11] and diabetic nephropathy [12] . However, the precise effect of FTY720 on proteinuria-induced tubulointerstitial inflammation has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%